INTERPERSONAL COMMUNICATION PERSPECTIVE OF THE QUR'AN AS-SAFFAT LETTER VERSE 102 - Hidayah, Masuratun (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
Interpersonal communication refers more to the process of closeness, for such intimacy of communication to purpose, that a message delivered to the recipient of the message can have the direct effect of building closeness and intimacy, so interpersonal communication begins with a psychological approach. The qur 'an has mentioned that ibrahim was one of the prophets who successfully educated children. The intimate, harmonious communication pattern was applied in an intimate, harmonious way of communicating the matter to him, so that what was delivered to his child would be well received. In delivering a message should use good words, so Islam places a high value on this principle related in the qur 'an surah as-saffat verse 102. Research uses qualitative research using the library study method (library research) of the Koran 'an surah as-saffat verse 102 and the written documents as a data gathering technique. Studies have shown that by relating a matter of controversy.